Latihan keterampilan sosial: Teknik meningkatkan kemampuan interaksi sosial skizofrenia - Putri, Anisa Novita (Universitas Muhammadiyah Malang, 2023)
Subject is a man. He is 34 years old. He often alone and do not want to interact with the people around him. The assessments use interviews, observations and psychological tests (Sack Sentence Completion Test, Wechsler Adult Intelligence Scale, Grafis, Wartegg, Thematic Apperception Test). The results of the assessment and referral from the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) concluded that the subject met the diagnostic criteria for 295.90 (F20.9) schizophrenic disorder with behavioral problems. Subject was did not want to interact with people around him, the subject often daydreams and speak by his selves. The intervention was carried out social skills training. Social skills training can improve social interaction. The social interaction that is taught aims to enable the subject to interact with people around him, establish communication or inviting people to speak and make eye contact during interactions. The research results showed that subject began to be able to interact with the people around him, but did not last long because sometimes the subject still choose to be alone. However, the subject is still accompanied with people around him. Subyeknya adalah seorang laki-laki. Dia berusia 34 tahun. Ia sering menyendiri dan tidak mau berinteraksi dengan orang-orang disekitarnya. Penilaiannya menggunakan wawancara, observasi dan tes psikologi (Sack Sentence Completion Test, Wechsler Adult Intelligence Scale, Grafis, Wartegg, Thematic Apperception Test). Hasil asesmen dan rujukan dari Diagnostic and Statistical Manual of Mental Disorders (DSM-5) menyimpulkan bahwa subjek memenuhi kriteria diagnostik gangguan skizofrenia 295,90 (F20.9) dengan masalah perilaku. Subjek tidak mau berinteraksi dengan orang disekitarnya, subjek sering melamun dan berbicara sendiri. Intervensi yang dilakukan adalah pelatihan keterampilan sosial. Pelatihan keterampilan sosial dapat meningkatkan interaksi sosial. Interaksi sosial yang diajarkan bertujuan agar subjek dapat berinteraksi dengan orang disekitarnya, menjalin komunikasi atau mengajak orang berbicara dan melakukan kontak mata saat berinteraksi. Hasil penelitian menunjukkan bahwa subjek mulai dapat berinteraksi dengan orang-orang disekitarnya, namun tidak bertahan lama karena terkadang subjek masih memilih untuk menyendiri. Namun subjek tetap ditemani oleh orang-orang disekitarnya.